The mystery of the Albany mummies - Lacovara, Peter; D'Auria, Sue (Excelsior Editions, 2018)
"This book recounts a fascinating tale of the mystery of the Albany mummies from their early acquisition in 1909, to their beloved status as Albany's Egyptian priest and priestess in the mid-twentieth century, to the present, when their mystery was solved through the intersection of historical scholarship and science and technology. Key to this story was the planning and installation of a major exhibition called GE Presents: The Mystery of the Albany Mummies, organized by the Albany Institute of History & Art and on view from September 21, 2013 until June 6, 2014"...Foreword
Includes bibliographical references and index
Keywords: Albany Institute of History and Art -- History; Albany Institute of History and Art; Mummies -- Egypt -- History; Mummy cases -- Egypt -- History; Mummies -- New York (State) -- Albany -- History; Mummy cases -- New York (State) -- Albany -- History; Egyptology -- New York (State) -- Albany -- History; Exhibitions -- New York (State) -- Albany -- History; Mumie; Egypt -- Kings and rulers -- History; Egypt -- Antiquities; Ägypten -- Altertum